2020
DOI: 10.1016/j.heliyon.2020.e04012
|View full text |Cite
|
Sign up to set email alerts
|

Gender differentials in technical efficiency of Ghanaian cocoa farms

Abstract: This study considers the presence of a gender gap in technical efficiency in Ghana's cocoa production sector. The two-stage double bootstrap data envelopment analysis (DEA) procedure was applied to estimate the biascorrected technical efficiency scores for male and female cocoa farm managers. The results indicate that there is a potential for male and female cocoa farm managers to increase output without altering the quantities of inputs employed. Applying the extended version of the Blinder-Oaxaca (B-O) decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…Also, the negative correlation of education with inefficiency is in accordance with research [15] . Meanwhile, the negative correlation between the number of family members and inefficiency is in accordance with studies [11,16].…”
Section: Source Of Inefficiency In Cocoa Productionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, the negative correlation of education with inefficiency is in accordance with research [15] . Meanwhile, the negative correlation between the number of family members and inefficiency is in accordance with studies [11,16].…”
Section: Source Of Inefficiency In Cocoa Productionsupporting
confidence: 90%
“…Also, to increase farmers' knowledge in cocoa production, education, and some basic skills such as reading and analysis are important. The research [11,15,16] conducted in Nigeria, Malaysia, and Ghana, respectively showed that farmers' education or knowledge has a positive correlation with production efficiency.…”
Section: The Characteristics Of Cocoa Farmersmentioning
confidence: 99%
“…Other studies have also tried to evaluate how credit impacts the welfare of farmers (Lakhan et al, 2020;Amanullah et al, 2019). Further, there are several studies on the technical efficiency of farmers of crops such as maize, rice, and cocoa (Danso-Abbeam et al, 2020;Martey et al, 2019;Abdulaai et al, 2018;Anang et al, 2017). However, there is little or no empirical evidence of the technical efficiency of cassava farmers, and most importantly, the impact of access to credit from RCBs on the technical efficiency of rural smallholder cassava farmers in rural Ghana; considering that currently, there are about 140 RCBs with close to 1000 branches scattered all over the country.…”
Section: Introductionmentioning
confidence: 99%
“…There is mixed literature about TE of plot managers. Most studies have documented that female plot managers have lower TE and TGRs compared to their male counterparts (see for example, Tesfaye et al, 2015 ; Sell et al, 2018 ; Danso-Abbeam et al, 2020 ). However, other studies such as Simonyan et al (2015) show contrary results.…”
Section: Introductionmentioning
confidence: 99%